Obstetric practices performed by nurse-midwives of a hospital natural birth center - Juliana Manoela dos Santos Freitas; Nádia Zanon Narchi; Rosa Aurea Quintella Fernandes
Abstract Objectives: To characterize the practices used by nurse-midwives in a Natural Birth Center (NBC) and to verify the maternal and neonatal outcomes. Method: This was a cross-sectional, documentary, retrospective study with a quantitative approach in which the medical records of 300 parturients who gave birth in a state hospital in the city of São Paulo were analyzed. The categories of the World Health Organization (WHO) composed the criteria adopted for the analysis of the obstetric practices. Fisher's exact test or the likelihood ratio and Student t-test were used. Results: The nurse-midwives mostly used category A practices of the WHO. There were no statistically significant associations between practices and perineal outcomes. There was a statistically significant association between the weight of the newborn and the number of neonatal complications, as well as between the delivery position of the primiparous women and clavicle fractures of the newborns. Conclusion and Implications for the practice: Evidence-based practices were followed by the nurse-midwives in the NBC analyzed. The maternal and neonatal outcomes were adequate. There is a need to improve care in the second stage of the delivery in order to avoid behaviors that reflect in neonatal complications. The study makes it possible to reflect on the importance of the continuous evaluation of the care provided.